The influence of cross-cultural competence on expatriate performance - Wang, Yuting (2017)
With an increasingly rapid economic globalization, competition in the global market has become more and more intense. To manage and allocate human resources effectively, sending employees to work abroad has gradually turned into a trend all over the world. Hence, the key to having competitive advantages in the global market lies in expatriate performance and how to enhance this performance becomes the focus of these companies. From previous literature, many factors have effects on expatriate performance, for example, individual factors, organizational factors, social factors and so on; however, past papers focus on learning information about expatriate performance through cross-cultural adjustments while research on factors of influence and expatriate performance mechanisms are very limited. Moreover, most studies concentrate on theoretical discussion and data is mostly based on companies owned by western countries; therefore, a gap in research exists: namely, in the Chinese context. The research objectives are Chinese employees hired by Chinese government-owned enterprises who have worked in Africa for at least three months in the past. Survey is applied for data collection and SPSS is used for data analysis. The survey started from 15th July to 31th July and 80 valid questionnaires were received in total. Several hypotheses are proposed; most of them are tested to be correct. The results are summarized as the following three statements. Firstly, the more competitive employees are in another culture, the easier and quicker they can adjust to local life and job responsibilities; thus, they will be more satisfied with their job and they can perform better than others. Secondly, job satisfaction and cross-cultural adjustment are two intermediate variables in the relationship between cross-cultural competence and expatriate performance. Lastly, demographic factors like age, gender, education background, marital status, past expat experience, and past experience in studying or living overseas, do not have significant correlations with the main variables. This study makes contributions to understand the influence of cross-cultural competence, job satisfaction, and cross-cultural adjustment on expatriate performance and the influence mechanism. The last chapter in this paper summarizes the main findings from data analysis and points out any limitations of this study, and direction for future studies. This paper enriches studies on expatriate performance and fills this gap in research.